Prehospital antiplatelet use and functional status on admission of patients with non-haemorrhagic moyamoya disease: a nationwide retrospective cohort study (J-ASPECT study). Issue 3 (15th March 2016) - Onozuka, Daisuke; Hagihara, Akihito; Nishimura, Kunihiro; Kada, Akiko; Nakagawara, Jyoji; Ogasawara, Kuniaki; Ono, Junichi; Shiokawa, Yoshiaki; Aruga, Toru; Miyachi, Shigeru; Nagata, Izumi; Toyoda, Kazunori; et al.
Abstract : Objectives: To elucidate the association between antiplatelet use in patients with non-haemorrhagic moyamoya disease before hospital admission and good functional status on admission in Japan. Design: Retrospective, multicentre, non-randomised, observational study. Setting: Nationwide registry data in Japan. Participants: A total of 1925 patients with non-haemorrhagic moyamoya disease admitted between 1 April 2012 and 31 March 2014 in Japan. Main outcome measure: We performed propensity score-matched analysis to examine the association between prehospital antiplatelet use and no significant disability on hospital admission, as defined by a modified Rankin Scale score of 0 or 1. Results: Propensity-matched patients who received prehospital antiplatelet drugs were associated with a good outcome on hospital admission (OR adjusted for all covariates, 3.82; 95% CI 1.22 to 11.99) compared with those who did not receive antiplatelet drugs prior to hospital admission. Conclusions: Prehospital antiplatelet use was significantly associated with good functional status on hospital admission among patients with non-haemorrhagic moyamoya disease in Japan. Our results suggest that prehospital antiplatelet use should be considered when evaluating outcomes of patients with non-haemorrhagic moyamoya disease.